A high-efficiency silicon-boron system impregnating agent formula and its preparation and application process

Through the high-efficiency silicon boron system impregnation agent formulation and vacuum impregnation process, the impregnation agent is penetrated deep into the electrolytic aluminum anode carbon block to form a boron oxide antioxidant film, solving the problems of limited protection effect and high production cost in the prior art, and achieving the effect of effectively reducing ineffective reactions and extending service life.

CN114016087BActive Publication Date: 2025-03-25黄治齐

Patent Information

Application Number
CN202111260354.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-28
Publication Date
2025-03-25
Estimated Expiration
2041-10-28

AI Technical Summary

Technical Problem

The prior art cannot effectively penetrate the impregnant into the interior of the electrolytic aluminum anode carbon block, resulting in limited protection effect, high production cost, and affecting product purity.

Method used

The high-efficiency silicon boron system impregnation agent formulation is adopted. The vacuum impregnation process allows the silicon boron system impregnation agent to penetrate into the internal pores of the anode carbon block in an organized manner to form a dense boron oxide antioxidant film, which enhances oxidation resistance and reduces ineffective reactions.

Benefits of technology

Effectively reduce the ineffective reaction of anode carbon blocks, extend the service life, reduce resource consumption, reduce production costs, and improve product purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114016087B_ABST
    Figure CN114016087B_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-boron system impregnating agent, which is a solution prepared by blending 0.001%-10% of silicon-based materials, 0.001%-10% of boron-based materials, no more than 10% of auxiliary agents, and 80%-99% of water in a certain proportion. The auxiliary agent is a thickener, and the amount of the thickener is adjusted according to actual requirements to control the viscosity of the impregnating agent to 0.01-10 Pa·s. The impregnating agent is organized and actively enters the internal pores of the anode by first applying negative pressure and then positive pressure, and is dried at low temperature. Under the high temperature environment during electrolysis, the impregnating agent forms a dense silicon-boron anti-oxidation film on the inner wall of the anode carbon block, and has a certain bonding strength. The silicon-based materials in the impregnating agent enhance its anti-oxidation property by improving the adhesion of the boron oxide film to the carbon anode, which can effectively prevent invalid oxidation in the pore channel of the anode carbon block, reduce air reactivity, and the silicon-boron carbon system forms a stable mesh structure in the pores of the anode carbon block, thereby effectively preventing slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of impregnants for carbon or graphite materials which are formed by mixing and pressing one or more amorphous carbon raw materials such as coal, carbon powder, petroleum coke, pitch coke, etc. and then sintering and finalizing them, in particular to an impregnant for electrolytic aluminum anode carbon blocks, and specifically to a formula for an efficient silicon-boron system impregnant and its preparation and application process. Background Art

[0002] The anode used in electrolytic aluminum is made of petroleum coke and asphalt coke as aggregates and coal tar as binder. This carbon block has a stable geometric shape after long-term roasting, so it is also called pre-baked anode carbon block. In electrolytic aluminum, the pre-baked anode is called the "heart" of the aluminum electrolytic cell by industry insiders. It consumes 500 kilograms per ton of aluminum, and pre-baked anode accounts for 10.29% of the total cost of the industry. Studies have shown that 33% of anode consumption is ineffective consumption, which mainly comes from the following aspects: 1. Oxidation of the hot anode surface in the air; 2. Slag and dust caused by differences in the reaction ability of local materials in the anode; 3. Ineffective reactions occurring at the pores when gas invades the porous carbon anode; 4. The final residual anode loss.

[0003] After the prebaked anode carbon block is sintered and formed, in order to reduce the ineffective consumption of the anode and increase the service life of the prebaked anode carbon block, the anode carbon block needs to be further treated. These treatment methods include: 1. Impregnation weight gain, using an impregnating agent to fill the gaps in the anode carbon block, increasing the weight of the anode carbon block per unit volume, thereby extending the service life of the carbon block in disguise; 2. Coating isolation, spraying an aluminum-based material coating on the anode to form an impermeable physical barrier; or applying a liquid bath to the surface after replacing the anode, and forming a coating after solidification; using the coating to isolate the gas to reduce ineffective reactions; 3. Reducing the inherent reactivity of carbon by adding chemicals such as boron. Among the above three treatment schemes, the first two mainly use physical methods for blocking or isolation. The third mainly uses chemical methods, using the chemical effect of boron on graphite oxidation, and its mechanism of action can be roughly summarized as follows: 1. The potential on graphite is replaced by boron to reduce the reaction activity; 2. Boron promotes the formation of larger graphite crystals, and larger graphite crystals are less reactive to oxygen; 3. A boron oxide film is formed on the graphite surface, blocking the active sites. However, studies have shown that to achieve the desired effect through the third option, the boron addition level needs to be very high, at least above 1000ppm, which will greatly increase the production cost. At the same time, from the above mechanistic analysis, it can be seen that boron plays a role by replacing in the graphitized structure. In the manufacturing process of carbon anodes, since the anode baking temperature is much lower than the graphitization temperature, no obvious graphitization can occur, so the role of boron in this process is limited.

[0004] The actual process of protecting the carbon anode by boron oxide coating can be In the prior art, aqueous solution impregnation of carbon anodes has been achieved by coating the anode surface with a boron-containing impregnant to form a protective film to protect the anode. The coating forms a coating covering the surface of the carbon anode and the inner surface of the surface opening micropores, so that the carbon anode has the ability to resist the diffusion and reaction of air and CO2 at high temperatures. However, during the application process, we found that this method has limited protection effect. The root cause is that the existing boron-containing impregnant cannot effectively penetrate into the interior of the anode carbon block, and can only stay on the surface of the anode carbon block or the shallower surface layer to form a protective film. In addition, the existing impregnation technology makes it difficult for the impregnant to penetrate into the core of the anode. Generally, the depth of impregnation can only be increased by extending the impregnation time. However, these methods not only increase production costs and reduce production efficiency, but also too long a treatment time will lead to excessive absorption of boron by the anode, thereby affecting the purity of the final product and failing to achieve industrial production.

[0005] Therefore, the present application aims to provide a new impregnating agent. By using the impregnating agent and cooperating with corresponding processes, the impregnating agent can penetrate into the interior of the anode, greatly reducing the ineffective reaction of the anode carbon block and saving resources. Summary of the invention

[0006] The purpose of the present invention is to solve the above-mentioned technical problems and provide a high-efficiency silicon-boron system impregnant formula and its preparation and application process. By using the impregnant and utilizing the vacuum impregnation method, the impregnant forming the silicon-boron system can be organized and completely immersed into the internal pores of the carbon anode, overcoming the problems of long impregnation time, insufficient impregnation depth, high raw material cost and unsatisfactory product purity in the prior art, and effectively dealing with the ineffective oxidation problems caused by the internal pore channels of the anode carbon block and the slagging phenomenon of the anode carbon block.

[0007] The technical solution adopted by the present invention to solve the technical problem is: a high-efficiency silicon-boron system impregnating agent formula, which is mainly composed of the following components by mass fraction: 0.001-10wt% silicon series; 0.001-10wt% boron series; auxiliary agent is not more than 10wt%; and the rest is water.

[0008] Furthermore, the impregnating agent is mainly composed of the following components: 0.1-5wt% of silicon-based substances; 0.1-5wt% of boron-based substances; the auxiliary agent is not more than 10wt%; and the rest is water.

[0009] Furthermore, the silicon-based material is one or more of silicate, silica gel, and colloidal silicon dioxide.

[0010] Furthermore, the boron-based substance is at least one of borax, boric acid, and metaborate.

[0011] Furthermore, the auxiliary agent is a thickener, specifically one or more of ammonium chloride and diethanolamine chloride. The viscosity of the impregnating agent is controlled within 0.01-10 Pa·s by adjusting the amount of the thickener according to actual requirements.

[0012] The high-efficiency silicon-boron system impregnant in the present invention is a solution, which is blended by silicon-based substances, boron-based substances and other additives in a certain ratio. The solution has a suitable viscosity, so that during impregnation, the impregnant can penetrate into the inner core of the anode carbon block, and after drying, the impregnant components are not easy to overflow from the pores of the carbon block. At high temperatures, the impregnant can form a dense boron oxide anti-oxidation film in the internal voids of the anode carbon block. The film has a certain adhesive force, and the silicon-based substances in the impregnant can enhance the (boron oxide film) antioxidant properties by improving the adhesion between the boron oxide film and the carbon anode, which can effectively prevent oxygen in the pore channel from contacting the anode carbon block, reduce the air reactivity of the anode carbon block, and the silicon-boron carbon system formed by the polymerization reaction at high temperature forms a stable network structure in the pores of the anode carbon block, thereby effectively preventing the anode carbon block from falling off.

[0013] The technical solution of the present invention also includes a method for preparing the above-mentioned high-efficiency silicon-boron system impregnating agent, which specifically includes the following steps: The first step is to calculate the mass of raw materials required for each component according to the mass fraction requirements of each component in the impregnating agent, weigh the corresponding weight of the raw materials, and save them separately for later use; The second step is to evenly mix the boron raw material with an appropriate amount of water at room temperature, and stir at a stirring speed of 30-150rpm to obtain solution I; The third step is to maintain the stirring speed of the previous step, divide the weighed silicon raw material into multiple portions, and add the silicon to solution I in batches, with an interval of 6 minutes between each addition, and obtain solution II after the addition is completed; The fourth step is to add an additive to solution II so that the viscosity of the solution reaches 0.01-10Pa·s, and then stir at 30-200rpm for 5-60min to obtain a silicon-boron system impregnating agent.

[0014] The technical solution of the present invention also includes an application method of the above-mentioned high-efficiency silicon-boron system impregnant, including the following steps: the first step is to place the prebaked anode carbon block in a vacuum tank, and evacuate the vacuum to a vacuum degree of 0.01-500Pa; the second step is to inject the impregnant into the tank, and the volume of the impregnant is controlled to exceed the volume of the impregnant liquid surface by more than 5% of the impregnation amount; the impregnant liquid surface refers to the impregnant liquid surface when it can just submerge the entire anode carbon block in the container. The third step is to apply a positive pressure of less than 0.6MPa to the vacuum tank, with a pressurization rate of not less than 4KPa / min, and maintain the pressure value for 0.1-3h, so that the impregnant fills the entire anode pores within the effective time;

[0015] Furthermore, a fourth step is included, namely, after the third step is completed, the anode carbon block is taken out and dried at a drying rate of 0.1-10kg water / (h·kg anhydrous material) to ensure that the anode surface and a depth of not less than 5cm below it are completely dried.

[0016] Furthermore, the fifth step is to transfer the anode carbon block treated in the previous step to the aluminum electrolytic cell, and continue to treat the anode carbon block by using the high temperature in the cell when the electrolytic cell is working. During normal operation, the temperature at different heights in the aluminum electrolytic cell is different, with the bottom temperature being 900-980°C and the top temperature being 500-600°C. The anode carbon block at the bottom of the electrolytic cell can use the high temperature conditions at the bottom to gradually turn the silicon-boron compound inside it into a glassy state, forming a stable secondary mesh structure film that isolates the air from the internal pores of the anode carbon block. The anode carbon block at the top can continue to dry by using the temperature at the top, which makes full use of the heat generated during the production process of the aluminum electrolytic cell and saves energy.

[0017] Principle of the present invention: At present, we can determine that the introduction of boron in the form of boron oxide or boric acid has a good performance in reducing the air reactivity of the carbon anode. At this time, if a small amount of colloidal silica is introduced, the concentration of boric acid can be reduced without affecting the antioxidant property, thereby reducing the cost. Experiments have proved that this is because silica gel can enhance the antioxidant property by improving the adhesion between the boric acid coating and the carbon anode. At the same time, we assist in the method of first negative pressure and then pressurized impregnation instead of ordinary impregnation or spraying, so that the impregnant can fully penetrate into the pores of sufficient depth inside the carbon anode in a shorter time. In such a silicon-boron system, not only does boron itself have the ability to reduce the reactivity of graphite, but also the boron oxide in the boron system interacts with silica gel to achieve a better anti-oxidation effect. Boron oxide is a good network former and has high viscosity at high temperature, while silica gel (mainly composed of silicon dioxide) also has very good viscosity and adsorption, and has strong high temperature resistance. In the high-temperature molten state, boron oxide and silica gel interweave with each other on the inner wall of the pore cavity to form a glassy secondary network structure film and structural crystal of the silicon-boron complex, which interacts with the carbon site in a small pore size to occupy the carbon site and form a surface covering film, and blocks the gas diffusion channel of the internal ineffective oxidation, comprehensively hindering its oxidation reaction, and reducing the apparent reaction rate on a large scale. Because it has a strong bonding strength and enhances structural stability, it can solve the phenomenon of slag and dust generation in electrolysis on a large scale, prolong the service life of prebaked anode carbon blocks, and greatly reduce invalid CO2 and CO gas emissions. Compared with the existing impregnants, the high-efficiency silicon-boron system impregnant provided by the present invention can adapt to the production and preparation of large-scale anode carbon blocks. It makes full use of the inherent pores inside the carbon aggregate particles, the pores between the aggregate particles in the ingredients, and the volatile gas exhaust channels and open pores formed in the raw anode during the roasting heat treatment process. The total porosity produced is generally 16%~25%, of which the open pores smaller than 1μm account for about 50%. Through vacuum impregnation, the impregnant that can form the silicon-boron system can be organized and completely immersed into the internal pores of the anode to a sufficient depth in a relatively short time.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention uses boron and silicon as the main impregnant raw materials. The impregnant can form a glassy secondary network structure film of silicon-boron composite on the inner wall of the pore cavity, which better isolates the contact between air and carbon, effectively reduces the invalid reaction of the anode carbon block, and greatly prolongs the service life of the anode.

[0020] 2. The viscosity of the impregnating agent of the present invention is adjusted within the range of 0.01-10Pa·s by a thickener, so that the particles in the impregnating agent can be suspended and have high dispersion stability; on the one hand, the impregnating agent can penetrate into the internal pores of the anode carbon block, rather than just staying on the surface of the carbon block or a limited depth below the surface; on the other hand, the impregnating agent is not easy to flow out after entering the anode pores, which effectively ensures the blocking of the internal pores of the anode, avoids the inconsistent reaction rates in various parts of the carbon block caused by the presence of a large number of pores, and can greatly reduce the slagging phenomenon of the anode carbon block.

[0021] 3. The raw materials of the impregnating agent of the present invention are easily available and inexpensive, and the silicon-boron composite can reduce the amount of boron used while enhancing the antioxidant property, thereby further saving production costs.

[0022] 4. The impregnating agent application process of the present invention can make full use of the heat of the electrolytic cell. The temperature at different heights in the aluminum electrolytic cell is different. Generally speaking, the temperature at the bottom of the electrolytic cell is 900-980°C, and the temperature at the top is 500-600°C. The anode carbon block at the bottom of the electrolytic cell can use the high temperature conditions at the bottom to gradually turn the silicon-boron compound inside it into a glassy state, forming a stable secondary mesh structure film to isolate the air from the contact with the internal pores of the anode carbon block. The anode carbon block at the top can continue to dry using the temperature at the top, thus making full use of the heat generated during the production process of the aluminum electrolytic cell and saving energy.

[0023] 5. The impregnating agent application process of the present invention enables the impregnating agent to penetrate into the deep pores of the anode faster by means of vacuum negative pressure, does not generate harmful gases, has no odor, does not pollute the environment, and is simple to operate, facilitating mechanized operation and industrialized production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a comparison chart of the residual rates of anode carbon blocks after being impregnated with the impregnants of Examples 1 to 4 of the present invention respectively;

[0025] Figure 2 is a comparison chart of dust rates of anode carbon blocks after being impregnated with the impregnants of Examples 1 to 4 of the present invention respectively;

[0026] Figure 3 is a comparison chart of the loss rates of anode carbon blocks after being impregnated with the impregnants of Examples 1 to 4 of the present invention respectively;

[0027] Figure 4 is a comparison diagram of the properties of the anode carbon block after and without the impregnation treatment of the present invention; DETAILED DESCRIPTION

[0028] The present invention will be further explained and illustrated below in conjunction with embodiments:

[0029] Example 1

[0030] This embodiment provides a high-efficiency silicon-boron system impregnating agent, which is a solution prepared by mixing borax, sodium silicate and water. By mass fraction, the boron content in the solution is 2%, the silicon content is 2%, and the rest is water.

[0031] The impregnating agent in this embodiment is prepared and used immediately when the electrolytic aluminum anode is replaced. The specific preparation and application method includes the following steps:

[0032] A. Weigh borax and sodium silicate according to the proportion of the impregnating agent components, put them into a stirring container, add water to dissolve, and mix them evenly at a stirring speed of 80 rpm;

[0033] B. Record the impregnating agent prepared in the previous step and store it for future use;

[0034] C. Place the prebaked anode carbon block in an impregnation tank and perform vacuum treatment to make the vacuum degree in the tank 300 Pa;

[0035] D. Inject the prepared impregnation liquid into the tank; apply a pressure of 0.3 Pa and maintain it for 50 minutes to allow the prebaked anode carbon block to fully absorb the impregnation agent;

[0036] E. Change the pressure in the impregnation tank to normal pressure, take out the impregnated anode carbon block and perform preliminary drying to ensure that the surface of the anode carbon block and the part with a thickness of not less than 5 cm below the surface are completely dry;

[0037] F. First, lift the residual anode out of the electrolytic cell, pick up the fallen blocks in the electrolytic cell, and then install the anode carbon blocks that have been preliminarily dried in the previous step onto the electrolytic cell; then start the electrolytic aluminum production. At this time, using the heat generated during electrolysis, the silicon-boron compound inside the anode carbon block at the bottom gradually changes into a glassy state, forming a stable secondary network structure film, and the anode carbon block on the top can continue to be dried.

[0038] The air reactivity test of the anode carbon block after step E was performed showed that the residual rate was 96.1%, the dust rate was 1.3%, and the loss rate was 2.6%.

[0039] Example 2

[0040] The difference between this embodiment and embodiment 1 is that the boron content of the high-efficiency silicon-boron system impregnating agent in this embodiment is 2%, the silicon content is 4%, and the remainder is water. The specific preparation and application steps are the same as those in the embodiment.

[0041] The air reactivity test of the anode after the treatment in step E of this embodiment was performed, and the result showed that the residual rate was 97.6%, the dust rate was 0.8%, and the loss rate was 1.6%.

[0042] Example 3

[0043] The difference between this embodiment and embodiment 1 is that the boron content of the high-efficiency silicon-boron system impregnating agent in this embodiment is 2%, the silicon content is 4%, and the remainder is water. The specific preparation and application steps are the same as those in the embodiment.

[0044] The air reactivity test of the anode after the treatment in step E of this embodiment was performed, and the result showed that the residual rate was 98.5%, the dust rate was 0.4%, and the loss rate was 1.1%.

[0045] Example 4

[0046] The high-efficiency silicon-boron system impregnating agent in this embodiment is prepared by mixing borax, silica gel, thickener, dispersant and water, wherein the boron content is 4%, the silicon content is 4%, the potassium chloride thickener and the hexadecyltrimethylammonium bromide dispersant content is 1%, and the rest is water.

[0047] The impregnating agent of the present invention should be prepared and used immediately when the electrolytic aluminum anode is replaced. The specific preparation and application method includes the following steps:

[0048] A. Weigh borax and silica gel according to the proportion of the above impregnating agent components, first put the borax in a stirring container, add water to dissolve it, and mix it evenly at a stirring speed of 80 rpm to form a solution, and then add silica gel to the solution in 10 portions;

[0049] B. Measure the viscosity of the solution obtained after the previous step, add a thickener or a dispersant according to the measurement result, and adjust the viscosity of the solution to 0.1 Pa·s; that is, the impregnating agent is obtained and stored for later use;

[0050] C. Place the prebaked anode carbon block into the impregnation tank and perform vacuum treatment to make the vacuum degree in the tank 300 Pa;

[0051] D. Add the prepared impregnating agent into the impregnation tank and apply a pressure of 0.3 Pa for 50 minutes to allow the impregnating agent to penetrate into the pores inside the anode carbon block;

[0052] E. Convert to normal pressure, introduce air, and dry the impregnated anode carbon blocks;

[0053] F. First, lift the residual anode out of the electrolytic cell, pick up the fallen blocks in the electrolytic cell, then install the anode carbon block that has been dried in the previous step onto the electrolytic cell, tighten the clamps, and seal it with insulation materials on all sides; then start the electrolytic aluminum production. At this time, using the heat generated during electrolysis, the silicon-boron compound inside the anode carbon block at the bottom will gradually turn into a glassy state, forming a stable secondary network structure film, and the anode carbon block on the top can continue to be dried.

[0054] Among them, the air reactivity test was performed on the anode dried in step E, and the result showed that its residual rate was 98.8%, the dust rate was 0.3%, and the loss rate was 0.9%.

[0055] Experimental demonstration:

[0056] According to the theoretical basis of the present invention, two experiments were carried out to prove the reliability of the invention idea: 1. Test of the impregnation effect of different silicon-boron concentrations; 2. Test of CO2 reactivity

[0057] Experiment 1: Test of the impregnation effect of different silicon-boron concentrations

[0058] The anodes in the above four embodiments were dried and then tested for air reactivity. The results are as follows: Figure 1-3 As shown. From the analysis of the experimental results, it can be seen that under the same impregnation process conditions, from the comparison of Examples 1 and 2, when the silicon-boron ratio is 2:1, the lower the air reactivity, the higher the residual rate is than when the silicon-boron ratio is 1:1; from the comparison of Examples 1 and 3, when the silicon-boron ratio is 1:1, the higher the silicon-boron content and the greater the concentration, the lower the air reactivity and the higher the residual rate. From the comparison of Examples 3 and 4, it can be seen that the effects of soluble silicates and insoluble silica gel are both very good, and the difference between the two is not much.

[0059] Experiment 2: CO2 reactivity test

[0060] The carbon anode that has not been impregnated and the carbon anode that has been treated with the impregnating agent of the present invention were tested for CO2 reactivity.

[0061] The CO2 reactivity of the anode is measured using the ISO12988-1 standard. The IOT-21 anode carbon dioxide reaction tester is used to measure the anode sample. The anode sample is exposed to a 200L / h CO2 hot gas flow to simulate the actual cell conditions. The CO2 gas flow temperature is 960°C at the bottom of the anode in the electrolytic cell. The exposure time is 9.5h. After the gas flow reaction is completed, the sample is cooled. The remaining part of the sample is the reaction residue. The more reaction residue, the lower the anode reactivity. The test results are as follows: Figure 4 As shown, it is obvious that the impregnating agent of the present invention can inhibit the generation of CO2 at the anode during electrolysis, and the effect is excellent.

[0062] The above are only some embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have combinations and modifications of the aforementioned various technical features. Without departing from the spirit and scope of the present invention, those skilled in the art may improve, modify, or replace the present invention with equivalents, or apply the structure or method of the present invention to other fields to achieve the same effect, which all fall within the scope of protection included in the present invention.

Claims

1. An application process of a high-efficiency silicon-boron system impregnating agent, characterized in that: The high-efficiency silicon-boron system impregnating agent is mainly composed of the following components by mass fraction: Silicon series 0.001wt%-10wt%; Boron series 0.001wt%-10wt%; The additive is not more than 10wt%; The remainder is water; The application process includes the following steps: the first step is to place the prebaked anode carbon block in a vacuum tank and evacuate the tank to a vacuum degree of 30-600 Pa; the second step is to inject the impregnant into the tank, and the volume of the impregnant is controlled to exceed the volume of the impregnant liquid surface by more than 5% of the impregnation amount; the impregnant liquid surface refers to the impregnant liquid surface when the entire anode carbon block can be just submerged in the container; the third step is to apply a positive pressure of less than 0.6 MPa to the vacuum tank, with a pressurization rate of not less than 4 KPa / min, and maintain the pressure value for 0.1-3 hours to allow the prebaked anode carbon block to fully absorb the impregnant.

2. The application process of the high-efficiency silicon-boron system impregnating agent according to claim 1 is characterized in that: The high-efficiency silicon-boron system impregnating agent is mainly composed of the following components by mass fraction: Silicon series 0.1wt%-5wt%; Boron series 0.2wt%-5wt%; The additive is not more than 10wt%; The remainder is water.

3. The application process of the high-efficiency silicon-boron system impregnating agent according to claim 1 is characterized in that: The silicon-based material is one or more of silicate, silica gel and colloidal silicon dioxide.

4. The application process of the high-efficiency silicon-boron system impregnating agent according to claim 1 is characterized in that: The boron-based substance is at least one of borax, boric acid, metaborate and borosilicate.

5. The application process of the high-efficiency silicon-boron system impregnating agent according to claim 1 is characterized in that: The auxiliary agent plays a role of modification and thickening, and the auxiliary agent is one or more of inorganic salts and inorganic gel mineral agents.

6. The application process of the high-efficiency silicon-boron system impregnating agent according to claim 1 is characterized in that: The preparation method of the high-efficiency silicon-boron system impregnating agent comprises the following steps: The first step is to calculate the mass of the raw materials required for each component according to the mass fraction requirements of each component in the impregnating agent formula, weigh the corresponding weight of the raw materials, and store them separately; the second step is to first mix the boron raw material with water at room temperature, and stir at a stirring speed of 30-200rpm to obtain solution I; the third step is to maintain the stirring speed of the previous step, divide the weighed silicon raw material into multiple portions, add the silicon to solution I in batches, and the interval time of each addition is 6 minutes. After the addition is completed, solution II is obtained; the fourth step is to add an auxiliary agent to solution II to make the viscosity of the solution reach 0.01-10Pa·s, and then stir at a stirring speed of 30-200rpm for 5-60min to obtain a silicon-boron system impregnating agent.

7. The application process of the high-efficiency silicon-boron system impregnating agent according to claim 1 is characterized in that: The method further comprises a fourth step, in which the anode carbon block is taken out from the vacuum tank and dried at a drying rate of 0.1-10 kg water / (h·kg anhydrous material) to ensure that the drying depth of the surface layer of the anode carbon block is greater than 5 cm.

8. The application process of the high-efficiency silicon-boron system impregnating agent according to claim 7 is characterized in that: The method also includes a fifth step, in which the anode carbon block processed in the fourth step is installed in the electrolytic cell, and the anode carbon block is further processed by utilizing the high temperature in the electrolytic cell when the electrolytic cell is working. At this time, the silicon-boron compound inside the anode carbon block gradually turns into a glassy state, forming a stable secondary network structure film, isolating the air from contact with the internal pores of the anode carbon block.

Citation Information

Patent Citations

  • Method and apparatus for impregnation of porous bodies for protection against oxidation

    US6228424B1

Cited By

  • A carbon material modified impregnating agent and its preparation method and application

    CN119776912A